1973
DOI: 10.1111/j.1532-5415.1973.tb01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Oral Glucose Load on Serum Immunoreactive Insulin, Free Fatty Acid, Growth Hormone and Blood Sugar Levels in Young and Elderly Subjects*

Abstract: In 29 healthy young adults and 22 ambulatory elderly subjects, a study was made of the effects of an oral glucose load on the levels of serum immunoreactive insulin (IRI), free fatty acids (FFA), growth hormone (HGH) and blood glucose. In the elderly, the pre‐load blood glucose and serum IRI levels were higher than in the younger group, reached the peak more gradually, and took longer to return to the baseline values. There was no significant difference in the serum FFA levels between the two groups until 3 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Most studies have demonstrated normal or increased insulin secretion as a function of aging following an oral or intravenous glucose load (3)(4)(5)(6)(7) Subjects. The study group consisted of 44 nonobese subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have demonstrated normal or increased insulin secretion as a function of aging following an oral or intravenous glucose load (3)(4)(5)(6)(7) Subjects. The study group consisted of 44 nonobese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…These subjects also have greater elevations of serum insulin levels, normal insulin binding, and marked insulin resistance manifested as both a decrease in insulin action at submaximal and maximal levels. 6 of the 17 elderly subjects fell into this group and they had a 53, 58, and 42% decrease in glucose disposal rates compared with the nonelderly group at insulin infusion rates of 15, 40, and 1,200 mU/M2 per min, respectively (Fig. 6 A).…”
mentioning
confidence: 99%
“…Body protein content Table 1 Insulin effectiveness on glucose metabolism in aging humans (vs young controls) (cf. Davidson, 1979;Borkan et al, 1983;Gumbiner et al, 1989;Chen et al, 1985;Pacini et al, 1988;Jackson, 1990;DeFronzo, 1979;Meneilly et al, 1987;Fink et al, 1983;Rowe et al, 1983;Broughton et al, 1991;Bonadonna et al, 1994;Ferrannini et al, 1996;Sandberg et al 1973;Fraze et al, 1987) 1994;Sandberg et al, 1973;Fraze et al, 1987;Groop et al, 1991;Shulman et al, 1980) Production normal or decreased suppression Oxidation normal or increased stimulation…”
Section: Protein Metabolism and Insulin Sensitivitymentioning
confidence: 99%
“…One way to approach this issue is to look at free-fatty acid (FFA) metabolism. FFA concentrations may be normal, increased or decreased in elderly individuals (Sandberg et al, 1973;Fraze et al, 1987), and this variability may depend on the subjects' insulin levels. Indeed, hyperinsulinemic older subjects may also have normal or decreased FFA (Sandberg et al, 1973;Fraze et al, 1987).…”
Section: Fat Metabolism and Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation